Biological activities of essential oils – a review - Rassem, Hesham H. A.; Nour, A. H.; R. M., Yunus (Pacific International Journal, 2018)
Essential oils are liquid preparations, produced from plant materials. These essential oils have a very high commercial value due to its properties. Plants essential oils are widely used in the various fields of industries, such as perfumery industries and pharmaceuticals and have a very high commercial value due to its therapeutic properties. Although essential oils showed a promising bioactivity in vitro, they could interact in plants with some components (Terpenes, acids, hydrocarbons, esters) and pH, thus many authors have reported that a significant effect of essential oils toward spoiling and pathogenic microorganisms could be achieved in vivo by using small amounts of oils. Different methods can be used to assess the bioactivity of essential oils. This study show benefits the essential oils and how using this essential oils in biological activities. It can be used oils extracted from different plants, whether they have a biological effect such as antioxidant or anti-bacteria or fungi. This review is a focus on which methods can use to determine biological activity for essential oils. Roads have also been paved on how to know Cytotoxicity of essential oils and how to find out.